2011
DOI: 10.1007/s11249-011-9763-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Molecular Level Structure of Polyethylene and Polytetrafluoroethylene on Their Tribological Response

Abstract: Crosslinks occur in polymers following irradiation and are used in computational simulations to mimic the effects of chain tangling. Here, the effect of crosslink density on the tribological behavior of atomic-scale models of polyethylene and polytetrafluoroethylene is determined using classical molecular dynamics simulations. In the simulations, oriented crosslinked surfaces are slid in different directions over a range of applied normal loads. The results indicate that, at the same normal load, the friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Lastly, a series of studies analyzed the effect of molecular structure, normal load, temperature, and sliding direction on the tribological performance of self-mated polytetrafluoroethylene (PTFE) and polyethylene (PE) surfaces using the REBO potential [71][72][73]. The two polymeric systems with various crosslink densities had inherently different degrees of structural integrity and rigidity.…”
Section: Reactions Between Solid Surfacesmentioning
confidence: 99%
“…Lastly, a series of studies analyzed the effect of molecular structure, normal load, temperature, and sliding direction on the tribological performance of self-mated polytetrafluoroethylene (PTFE) and polyethylene (PE) surfaces using the REBO potential [71][72][73]. The two polymeric systems with various crosslink densities had inherently different degrees of structural integrity and rigidity.…”
Section: Reactions Between Solid Surfacesmentioning
confidence: 99%
“…Our level of cross-linking was chosen to impart some level of structural integrity in the form of entanglement in order to effectively simulate self-mated sliding of the system under the influence of an externally applied load. An in-depth analysis of the effects of the degree of cross-linking on friction behavior for our simulated PTFE and PE systems was conducted by Chiu et al [34]. That study showed that the friction force increases with cross-link density for fixed, constant normal load; however, for the range of normal load considered in that particular study, similar to that used here, a substantial change in friction coefficient was not observed.…”
Section: Methodsmentioning
confidence: 58%
“…Physically, this cross-linking is intended to mimic the effects of the structural reinforcement in semicrystalline polymers arising from entanglement, which takes place on a longer length scale than those accessible to these atomiclevel simulations. The effects of changing this cross-link density are discussed elsewhere [34]. Each PTFE crystal or slab contains seven layers of chains for a total thickness of 4.0 nm and a sliding surface area of 4.5 nm 9 4.5 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical formalism used here has been successfully used in recent years to describe atomistic simulations investigating the tribological and mechanical properties of a variety of carbon-based systems, including nanomaterials. 10,22,[27][28][29] In order to accurately simulate the amorphous character of a-C nanoparticles, we first heated a large, periodic system of crystalline diamond to a temperature of 8000 K. After allowing the system to become fully disordered, the system was rapidly quenched to 300 K at a rate of 100 K/ps; from this periodic a-C structure, spheres with diameters of 2, 3, 4, and 5 nm were extracted. In addition to these non-hydrogenated nanoparticles, partially hydrogenated nanoparticles were also formed.…”
Section: Methodsmentioning
confidence: 99%